「タモクテキ エイセイ データ ジュシン システム リヨウ」 「エイセイ ト チジョウ カンソク ヒカク ニヨル キョクイキ キスイケン カイセキ」 ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 平沢, 尚彦; ヒラサワ, ナオヒコ; 山内, 恭; ヤマノウチ, タカシ; 江尻, 全機; エジリ, マサキ; Hirasawa, Naohiko; Yamanouchi, Takashi; Ejiri, Masaki (1994)
P(論文) 本研究小集会の目的は1 : 衛星データを使って極域気水圏の物理的パラメータを抽出する方法を地上観測データと比較しながら検討すること, 2 : 極域における興味深い研究テーマをさらに研究していくために必要となるセンサーや衛星の軌道要素を検討し, 昭和基地で今後受信したい衛星を明らかにすることである。本会は1994年1月20日, 極地研講義室において行われ, 出席者は約30名であった。NOAAまたはDMSPのデータを使った大陸氷床の表面状態の解析, ERS, JERSのデータを使った海氷の検出, 海氷・氷床域においてNOAAの多波長放射データを使った雲の検出と放射収支に及ぼす雲の効果, 衛星とレーダー観測の比較, 可視・近赤外領域においての氷床表面付近での多重散乱に関するモデリングなどについて本会で議論された。最後に, 今後, 昭和基地でRADARSAT, ERS-2,NOAA, DMSP, SeaStarのデータ受信について要望があった。 The purposes of the workshop are 1 : to discuss algorithms to derive parameters of the polar atmosphere and hydrosphere using satellite data together with surface observations to be compared, and 2 : to select the satellites to be received at Syowa Station through discussion about their sensors and the orbital elements. It was held on January 20,1994 at the National Institute of Polar Research (NIPR), the number of participants being about 30. The contents of the workshop are (1) analysis of the character of the ice sheet surface by NOAA or DMSP, (2) detection of sea ice distribution by ERS or JERS, (3) detection of cloud by NOAA multi-chanel radiation data and effect of clouds on radiation budget and (4) a modeling about multi-scattering in the snow layer of ice sheet surface in the range of visible to near infrared. Finally, future requirements for the RADARSAT, ERS-2,NOAA, DMSP and SeaStar data at Syowa Station were discussed. departmental bulletin paper